Figures 79–92 in Revisiting Potter Cove, King George Island, Antarctica, 12 years later: new observations of marine benthic diatoms - Al-Handal, Adil Y.; Torstensson, Anders; Wulff, Angela (Zenodo, 2022)
Figures 79–92: Marine benthic diatoms in Potter Cove, King George Island, Antarctica, summer 2015. (79) Gyrosigma arcuatum. (80) Gyrosigma fasciola. (81) Gyrosigma cf. obscurum. (82) Pleurosigma eudon var. kerguelensis. (83) Pleurosigm diversestriatum. (84) Pleurosigma strigosum. (85) Amphora gourdonii. (86) Amphora marina. (87, 88) Amphora sp. 1. (89) Amphora sp. 2. (90) Cylindrotheca closterium. (91, 92) Fragilariopsis cylindrus. Published as part of Al-Handal, Adil Y., Torstensson, Anders & Wulff, Angela, 2022, Revisiting Potter Cove, King George Island, Antarctica, 12 years later: new observations of marine benthic diatoms, pp. 81-103 in Botanica Marina (Warsaw, Poland) 65 (2) on page 94, DOI:10.1515/bot-2021-0066, http://zenodo.org/record/11000147